Intra-individual biomechanical effects of a non-microprocessor-controlled stance-yielding prosthetic knee during ramp descent in persons with unilateral transfemoral amputation. (February 2019) - Okita, Yusuke; Yamasaki, Nobuya; Nakamura, Takashi; Mita, Tomoki; Kubo, Tsutomu; Mitsumoto, Atsuko; Akune, Toru
Background: A stance-yielding mechanism for prosthetic knees may reduce lower limb loading during specific activities, but quantitative data are insufficient. Objectives: To clarify the biomechanical effect of a non-microprocessor-controlled stance-yielding mechanism on ramp descent for individuals with unilateral transfemoral amputation. Study design: Intra-subject intervention study. Methods: Seven individuals with unilateral transfemoral amputation underwent three-dimensional motion analysis of ramp descent with and without activating a stance-yielding mechanism. Regarding early-stance internal joint moment and ground reaction force, whole-group and subgroup analyses stratified by stance prosthetic knee flexion were performed to verify differences in prosthetic side and contralateral limb loading between conditions. Results: Whole-group analysis revealed significant reduction in early-stance prosthetic knee extension moment with stance-yielding mechanism activation. Changes in prosthetic side hip extension moment and contralateral limb loading were inconsistent between conditions. Subjects with prosthetic stance knee flexion walked slower with a smaller stride and greater increase in aft ground reaction force and ankle dorsiflexion moment when stance-yielding was activated. Conclusion: Stance-yielding mechanism has a biomechanical potential to decrease excessive knee hyperextension. However, prosthetic side stance knee flexion induced by the stance-yielding mechanism might not necessarily reduce the mechanical load on residual hip or contralateral lower limb joints. Clinical relevance: This study showed individual variability in the possibility of reducing the load on the remaining lower limb when using a non-microprocessor-controlled stance-yielding knee. This suggests that individualized prosthetic management and monitoring the activities of individuals wearing a stance-yielding prosthetic knee are crucial to maximize the benefits of stance-yielding prosthetic knees.